2018
DOI: 10.4103/abr.abr_214_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of miR-21 Inhibition and its Impact on Cancer Susceptibility Candidate 2 Long Noncoding RNA in Colorectal Cancer Cell Line

Abstract: Background:Both microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been shown to have a critical role in the regulation of cellular processes such as cell growth and apoptosis, as well as cancer progression and metastasis. lncRNAs are aberrantly expressed in many diseases including cancer. Although it is well known that miRNAs can target a large number of protein-coding genes, little is known whether miRNAs can also target lncRNAs. In the present study, we determine whether miR-21 can regulate lncRNA ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…22 In addition, CASC2 was downregulated in glioma tissues and cell lines to play a suppressor in a variety of human cancer cells. [22][23][24][25][26][27][28] Due to its wide arrange of functions of CASC2 in the tumorigenesis prompted us to ask whether CASC2 could be a tumor suppressor in PTC formation.…”
Section: Introductionmentioning
confidence: 99%
“…22 In addition, CASC2 was downregulated in glioma tissues and cell lines to play a suppressor in a variety of human cancer cells. [22][23][24][25][26][27][28] Due to its wide arrange of functions of CASC2 in the tumorigenesis prompted us to ask whether CASC2 could be a tumor suppressor in PTC formation.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a kind of small non-coding RNAs, which regulate the expression of target genes through promoting the degradation of target mRNA, via incompletely binding with the 3′-UTR of target proteins or inducing translational repression 4,5. Substantial evidence demonstrates that dysregulation of miRNAs is associated with the development and metastasis of several cancers, and miRNAs might be the potential treatment targets in cancers 6–9.…”
Section: Introductionmentioning
confidence: 99%
“…For the 5 identified lncRNA markers, CASC2 has been reported to be associated with colorectal cancer [33][34][35]. Studies have revealed that the deregulation of CASC2 by miRNA hsa-mir-21 and hsa-mir-18a increases the proliferation and migration of cancer cells in colorectal cancer [33][34][35].…”
Section: General Commentsmentioning
confidence: 99%